ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MUTU PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RSUD DR RASIDIN PADANG TAHUN 2012 - Nita Ariani (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Documentation is one of the important aspect in providing nursing care, because it is an indicator of being accounta ble as a nurse The purporse of this research was to analyse the factors (knowledge, attitude, motivation and supervision) which were related to the quality yad nursing care documentation (completeness and accuracy) at RSUD dr Rasidin Padang. This study used the quantitative research to examine the relationship using cross sectional approach The sample of the study consisted of 37 nurse providers working at selected nursing units, such as medical, surgical, and pediatrics units. Instrument was developed by the researcher to measure the level of attitude, motivation, supervision, and quality of documentation. The result of this study showed that the nurses have the average age of 32 years, majority female nurses(91,9%), have DIII nu rsing education (94,6%.) with the average years of working was 4 years. The majority of nurses (64.9%) have high knowledge on the quality of nursing care documentation . Fifty nine and half percents (59.5%) nurses have a positive attitude on the quality of nursing care documentation. About 56.8% of nurses have high motivation on the quality of nursing care documentation Only 40.5% nurses who perceived that the head nurses were good in supervison There was a relationship between knowledge, atti tude, motivation and supervision with the quality of of nursing care documentation at nursing wards. There was a dominant factors between attitude of nurses (p value = 0,041) and OR 14,72 Followed by motivation factor with a p value value = 0,002 and OR on the quality of nursing care. Documentation based on the result of this study, it is recommended that the management of RSUD dr Rasidin to from nursing committee, provide education and training on motivation, or to empower nursing staffs by motivation them on nursing care documentation. Key words: documentation, knowledge, attitude, motivation and supervision supervise